2016
DOI: 10.3109/09273948.2016.1139730
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Vogt–Koyanagi–Harada Disease and Development of ‘Sunset Glow Fundus’ Predict Worse Retinal Sensitivity

Abstract: Chronic recurrent presentation and development of complications and 'sunset glow fundus' are associated with a worse sensitivity outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…Chronic recurrent VKH disease is significantly associated with more severe anterior segment inflammation at presentation and a worse visual acuity and mean retinal sensitivity at last follow‐up compared with initial‐onset acute VKH disease (Abu El‐Asrar et al. , ). Studies using laser flare‐cell meter demonstrated that both aqueous flare values and cell counts were significantly higher in patients with chronic recurrent VKH disease than those with initial‐onset acute VKH disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic recurrent VKH disease is significantly associated with more severe anterior segment inflammation at presentation and a worse visual acuity and mean retinal sensitivity at last follow‐up compared with initial‐onset acute VKH disease (Abu El‐Asrar et al. , ). Studies using laser flare‐cell meter demonstrated that both aqueous flare values and cell counts were significantly higher in patients with chronic recurrent VKH disease than those with initial‐onset acute VKH disease.…”
Section: Discussionmentioning
confidence: 99%
“…) and mean retinal sensitivity (Abu El‐Asrar et al. ). In addition, the development of ‘sunset glow fundus’ was significantly associated with the development of any complication of cataract or glaucoma or subretinal neovascular membranes (Abu El‐Asrar et al.…”
Section: Discussionmentioning
confidence: 99%
“…The poor response to therapy, among patients with a chronic recurrent granulomatous AS inflammation has been described [ 20 , 25 ]. Moreover, this subset of patients has more complications [ 8 , 26 ] and a trend to have more severe ocular and systemic manifestations of the disease. El Asrar et al found a higher frequency of posterior synechiae and anterior chamber cells at diagnosis in patients who later turned to have this chronic condition [ 8 , 26 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Following this initial uveitic phase, a significant group of patients may develop chronic granulomatous inflammation, and progressive depigmentation of the fundus resulting in "sunset glow fundus" appearance and/or chorioretinal atrophy (Figure 2). These clinical findings frequently result from insufficiently treated or from a late diagnosis, and they have been associated with poorer functional outcomes [19][20][21].…”
Section: Clinical Findingsmentioning
confidence: 99%